1990
DOI: 10.1111/j.1600-0749.1990.tb00294.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Phenotypic Alteration of Human Melanoma Cells Induced by Differentiating Agents: Heterogeneous Effects on Cellular Growth and Morphology, Enzymatic Activity, and Antigenic Expression

Abstract: Sodium butyrate (butyrate), 5-azacytidine (5Aza-C), dimethyl sulfoxide (DMSO), and dimethyl formamide (DMF) were applied to a human melanoma cell line for the purpose of inducing pigmentation and terminal differentiation. The results are summarized as follows: 1) butyrate, DMSO, and DMF had a strong cytostatic effect, arresting cells in the G1 phase of the cycle; 2) butyrate caused a morphological change to spindle shape whereas DMSO and DMF produced rounded cells, without affecting the levels of vimentin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Star-shaped cells appeared in cultures treated with 3 mM VPA. Takahashi et al studied the impact of another two HDACis on differentiation in human melanoma cells: sodium butyrate (NaB) and DMSO [47]. They showed that NaB caused the formation of star-shaped cells, whereas DMSO did not affect the cell morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Star-shaped cells appeared in cultures treated with 3 mM VPA. Takahashi et al studied the impact of another two HDACis on differentiation in human melanoma cells: sodium butyrate (NaB) and DMSO [47]. They showed that NaB caused the formation of star-shaped cells, whereas DMSO did not affect the cell morphology.…”
Section: Discussionmentioning
confidence: 99%
“…After transfer of proteins onto nitrocellulose membrane, immunostaining was carried out as described elsewhere [19]. In order to assess the potential of SCF and c-KIT as differentiation markers for melanocytes, human melanoma cells (MM96E and MM138) were cultured in the presence of sodium butyrate (1.5 raM) or HMBA (10 raM), since these doses were the most effective for induction of various phenotypic alterations in these cell lines with minimal cellular damage [18,20]. After incubation with each drug for 48 h, cells were harvested with trypsin, washed in PBS (pH 7.2), and subjected to Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the present study was therefore to compare the l.ocalisation of SCF in normal skin, melanocytic naevi, and malignant melanomas and compare it with the distribution of its receptor, c-KIT. In addition, sodium butyrate and hexamethylene bisacetamide (HMBA), which have been reported to induce various phenotypic alterations in melanoma cells [18,20], were applied to cultured human melanoma cells, to determine whether SCF and/or c-KIT could serve as markers for differentiation of pigment cells.…”
Section: Introductionmentioning
confidence: 99%
“…Butyrate enhances the cellular content of histone HI0 [IS, 33, 341, and it alters the extent of acetylation [33 -391 phosphorylation [33,38] and methylation [38] ofhistones or other chromosomal proteins. Melanoma cell lines like B16 [40-421, treated with butyrate, cease to proliferate rapidly and start to synthetize melanin in a tyrosine-dependent manner [43] but unlike MEL cells the induction of differentiation is reversible upon removal of the inducing agent. We have studied the regulation of the HI0-mRNA accumulation during the various phases of the butyrate treatment of these cells and after releasing them into an butyrate-free medium.…”
mentioning
confidence: 99%